A cooperative of their own: Gender implications on renewable energy cooperatives in Germany. (February 2023) - Karakislak, Irmak; Sadat-Razavi, Pantea; Schweizer-Ries, Petra
Abstract: Renewable energy cooperatives are crucial for local communities to initiate energy transition. With a mixed-methodological approach, this paper analyses the participation of women in renewable energy cooperatives in Germany and reveals the socio-cultural barriers. This study presents an intersectional analysis that integrates gender with other socio-cultural categories and identities within the social context of cooperatives. This study presents the results from a sex ratio analysis of energy cooperatives (N = 388), online interviews (N = 161), and semi-structured interviews (N = 9). Results show that a lack of awareness of opportunities, financial resources, and time for volunteer-based workload and the lack of recognition of social inequalities in the cooperatives hinder women from actively taking part in leadership roles. This study concludes by discussing how contribution to localised renewable energy production reflects differently on genders. It also provides suggestions such as mentorship and diversity programs that would allow more women to take management roles and encourage a more inclusive and fair transition for all.